Learning while working : success stories on workplace learning in Europe - (:unkn) unknown (Publications Office of the European Union, 2011)
This report presents an overview of key trends in workplace learning and takes stock of previous research carried out by Cedefop and other European and international organisations. In considering key success factors and challenges related to workplace learning, the report examines effective policies, strategic partnerships, structures, and instruments that aim to expand adult learning in the workplace. (BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 1.5.3 Betriebliche Weiterbildung; S 3.2.1 KMU, Klein- und Mittlere Unternehmen; P 2.2 An- und Ungelernte; P 3.2.1 Ausbilder; I 2.2 Europa; Lebenslanges Lernen; Betriebliche Berufsausbildung; Betriebliche Weiterbildung; Lernen am Arbeitsplatz; Kompetenzentwicklung; Ausbildungsbereitschaft; Weiterbildungsbereitschaft; Klein- und Mittelbetrieb; Geringqualifizierter; Ausbilder; Europa